EP.WE.470Emergency General Surgery during the first COVID peak, a single centre experience. (28th October 2021) - Paramjothy, Kiara; Dosis, Alexios; Lim, Jieqi; Reveendran, Dharsshini; Lockwood, Sonia
Abstract: Aims: The COVID-19 pandemic brought significant changes on all aspects of health care. We aimed to conduct a retrospective review of the trends in general surgical and vascular procedures during the first peak following the cessation of all elective activity. Methods: All general and vascular procedures performed during April 2020 were included in the study. Peri-operative data were extracted from electronic patient records. We looked into operation notes, COVID status and post-operative complications. Descriptive analysis was performed using Microsoft Excel software. Results: Table 1 shows a breakdown of the 54 operations performed. There were 47 patients, with a male to female ratio at 1:1. Mean age was 46.9 years. There were 6 expedited cases but none elective. Mean duration of symptoms prior to presentation was 8.3 days. Laparoscopic work was kept to a minimum. A consultant was present for 63% of the cases. There were only 2 COVID positive patients, but the majority (74%) were not tested. 20% of patients suffered a complication requiring an intervention. 6/54 had an unplanned return to theatre and there were 5 deaths in total. Conclusion: The number of procedures during the first peak was significantly reduced following the uncertainty around the novel coronavirus. In accordance with the initial intercollegiate guidance, patients were managed conservatively where possible. The high complication rate is indicative of the often-late presentation due to hospital fear following the outbreak of SARS‐CoV‐2.